Audi Alteram Partem: An Experiment on Selective Exposure to Information - Giovanni Montanari; Salvatore Nunnari (Center for Economic Studies and ifo Institute (CESifo), 2023)
We report the results of an experiment on selective exposure to information. A decision maker interested in learning about an uncertain state of the world can acquire information from one of two sources which have opposite biases: when informed on the state, they report it truthfully; when uninformed, they report their favorite state. A Bayesian decision maker is better off seeking confirmatory information unless the source biased against the prior is sufficiently more reliable. In line with the theory, subjects are more likely to seek confirmatory information when sources are symmetrically reliable. On the other hand, when sources are asymmetrically reliable, subjects are more likely to consult the more reliable source even when prior beliefs are strongly unbalanced and this source is less informative. Our experiment suggests that base rate neglect and simple heuristics (e.g., listen to the most reliable source) are important drivers of the endogenous acquisition of information.
Keywords: C91; D81; D83; D91; 330; information acquisition; biased information sources; selective exposure; echo chambers; confirmation bias; base rate neglect; laboratory experiment